Effects of Manipulating Circulating Bile Acid Concentrations on Postprandial GLP-1 Secretion and Glucose Metabolism After Roux-en-Y Gastric Bypass - Jonsson, Isabella; Bojsen-Møller, Kirstine N.; Kristiansen, Viggo B.; Veedfald, Simon; Wewer Albrechtsen, Nicolai J.; Clausen, Trine R.; Kuhre, Rune E.; Rehfeld, Jens F.; Holst, Jens J.; Madsbad, Sten; Svane, Maria S. (Frontiers in Endocrinology, 2021)
Background: Altered bile acid (BA) turnover has been suggested to be involved in the improved glucose regulation after Roux-en-Y gastric bypass (RYGB), possibly via stimulation of GLP-1 secretion. We investigated the role of exogenous as well as endogenous BAs for GLP-1 secretion after RYGB by administering chenodeoxycholic acid (CDCA) and the BA sequestrant colesevelam both in the presence and the absence of a meal stimulus. Methods: Two single-blinded randomized cross-over studies were performed. In study 1, eight RYGB operated participants ingested 200 mL water with 1) CDCA 1.25 g or 2) CDCA 1.25 g + colesevelam 3.75 g on separate days. In study 2, twelve RYGB participants ingested on separate days a mixed meal with addition of 1) CDCA 1.25 g, 2) COL 3.75 g or 3) COL 3.75 g x 2, or 4) no additions. Results: In study 1, oral intake of CDCA increased circulating BAs, GLP-1, C-peptide, glucagon and neurotensin. Addition of colesevelam reduced all responses. In study 2, addition of CDCA enhanced meal-induced increases in plasma GLP-1, glucagon and FGF-19 and lowered plasma glucose and C-peptide concentrations, while adding colesevelam lowered circulating BAs, but did not affect meal-induced changes in plasma glucose or measured gastrointestinal hormones. Conclusion: In RYGB-operated persons, exogenous CDCA enhanced meal-stimulated GLP-1 and glucagon secretion, but not insulin secretion, while the BA sequestrant colesevelam decreased CDCA-stimulated GLP-1 secretion, but did not affect meal-stimulated GLP-1, C-peptide or glucagon secretion or glucose tolerance. These findings suggest a limited role for endogenous bile acids in the acute regulation of postprandial gut hormone secretion or glucose metabolism after RYGB.